2020
DOI: 10.1002/adma.202000969
|View full text |Cite
|
Sign up to set email alerts
|

A Behavior‐Learned Cross‐Reactive Sensor Matrix for Intelligent Skin Perception

Abstract: Recently, the realization of artificial sensory systems mimicking the biological perception has been intensively pursued for the next generation neuromorphic electronics and humanoid robots. Particularly, an artificial somatosensory system which can emulate the functions of the biological skin and body sensation is considered to have a great potential in achieving highly integrated and neuromorphic sensory network. The biological somatosensory system is a complex sensory network, which is composed of sensory n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…To distinguish between sensory memory and short‐term memory, memristors possessing second‐order or higher‐order state variables are used so that the first‐stage sensory memory is stored in the internal states of the devices, such as ion distribution, that the device resistances are unchanged, whereas the following stage of short‐term memory is formed by the measurable resistance changes due to the accumulated changes of the internal states. [ 242,243 ] Recent reviews [ 244,245 ] have also surveyed the reports on the integration of sensors, artificial sensory neurons, and synapses [ 84,138,246–261 ] that suggest a trend of the integration of sensing, memory, and computing [ 262,263 ] (Figure 4b). Future neuromorphic electronic systems may also benefit from sensory memory in executing attentive novelty detection tasks and so on.…”
Section: Computational Levelmentioning
confidence: 99%
“…To distinguish between sensory memory and short‐term memory, memristors possessing second‐order or higher‐order state variables are used so that the first‐stage sensory memory is stored in the internal states of the devices, such as ion distribution, that the device resistances are unchanged, whereas the following stage of short‐term memory is formed by the measurable resistance changes due to the accumulated changes of the internal states. [ 242,243 ] Recent reviews [ 244,245 ] have also surveyed the reports on the integration of sensors, artificial sensory neurons, and synapses [ 84,138,246–261 ] that suggest a trend of the integration of sensing, memory, and computing [ 262,263 ] (Figure 4b). Future neuromorphic electronic systems may also benefit from sensory memory in executing attentive novelty detection tasks and so on.…”
Section: Computational Levelmentioning
confidence: 99%
“…Recently, Lee et al reported a behavior-learned cross-reactive sensor array with artificial perception technology based on a machine learning process to detect and distinguish various intermixed stimuli. Unlike most previous wearable sensors focused on the configuration of sensor devices and nanostructured materials engineering technology, the pattern recognition and multimodal perception for intermixed stimuli are possible by adopting a machine learning algorithm [ 161 ]. The combination of carbon- and textile-based wearable sensor arrays with a machine learning algorithm could become a viable approach to realize practical wearable applications that can detect and discriminate multiple stimuli in health monitoring systems.…”
Section: Challenging Issues and Future Routes; Carbon- And Textilementioning
confidence: 99%
“…Particularly, because the stimuli such as strain and pressure can affect the output signals of each other, precise determination of each stimulation might be difficult unless a proper discrimination of the sensing signals is performed. In fact, by using a machine-learning-based approach, it has been shown that the discrimination of temperature, strain, and pressure could be possible ( Lee et at., 2020 ). However, such approaches may require a considerable number of datasets for training to achieve high accuracy for identifying the mixed stimuli.…”
Section: Introductionmentioning
confidence: 99%